Identifying Key Predictors of Academic Engagement in Low-Performing Schools: The Interplay Between Social Context and Psychological Factors - Bulqia Mas'ud; Zulfianah Sunusi; Zuhdiah Zuhdiah; Okky Naomi Sahupala (Edukasia)
Research shows that students’ academic engagement is influenced by both social and psychological factors. This study aims to explore which aspects of social context (family, school, and community), and psychological traits (self-efficacy, perseverance, and resilience) affect academic engagement. A quantitative approach with correlational design and multiple regression analysis was used. The research included 437 students from primary and junior high schools, focusing on 15 schools identified as having low to medium academic performance. The findings indicate that within the social context, family-related factors, particularly parental supervision, along with the number of teachers, are significant predictors of academic engagement. Among psychological factors, self-efficacy, perseverance, and resilience all positively influence engagement, with self-efficacy being the most significant. Overall, psychological factors were found to have a stronger impact on academic engagement than social factors. The study concludes that despite challenges such as socioeconomic disadvantages and limited support from schools and communities, students can still achieve better academic outcomes if they develop key psychological strengths. Providing interventions that promote self-belief and motivation can help students cultivate self-efficacy, perseverance, and resilience, which are critical for their future success. This highlights the importance of nurturing these traits to improve academic engagement and achievement.